William Shippen papers - Shippen, William, 1736?-1808.
ALS (1770 October 10) written by Shippen to his brother, Edward Shippen, relating to family matters; ALS (1778 April 12) from Shippen to Elbridge Gerry concerning Benjamin Rush; ALS (1760 February 8) from Shippen to Nathanael Greene regarding Shippen's upcoming court-martial for financial irregularities within the Continental Army medical dept., and mentioning the trial of Benedict Arnold; and receipted account (1752-1765) for medical services rendered to the family of Edward Shippen.
Typescript version of the letter to Elbridge Gerry is also available.
Physician and educator of Philadelphia, Pa., and chief of the medical dept., Continental Army.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Arnold, Benedict, -- 1741-1801.; Gerry, Elbridge, -- 1744-1814 -- Correspondence; Greene, Nathanael, -- 1742-1786 -- Correspondence; Rush, Benjamin, -- 1746-1813.; Shippen, Edward, -- 1729-1806 -- Correspondence; United States. -- Continental Army -- Finance; Courts-martial and courts of inquiry; Medicine -- Practice -- Pennsylvania -- Philadelphia; Pennsylvania -- History -- Revolution, 1775-1783.; Philadelphia (Pa.) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Medical care; Educators; Physicians